Pengaruh Pembelajaran Sistem Blok dengan Pendekatan Project Based Learning Terhadap Kesiapan Kerja Peserta Didik Program Keahlian Kuliner SMKN 9 Padang - Bunda, Nissi Andesta Permata; Hidayati, Abna; Bentri, Alwen; Amilia, Winanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to determine the influence of block system learning with a project-based learning approach on the work readiness of students of the culinary skills program of SMKN 9 Padang. The population in this study is class XII students in 2024. The sample of this study is 55 respondents. Data collection in this study uses observation, interview and questionnaire techniques using a Likert scale. This study uses descriptive analysis, classical assumption test, multiple regression analysis and hypothesis test. The results of the study showed that block system learning (X1) did not have a significant effect with a calculation result of -5.324 on the work readiness of students (Y). Project-based learning (X2) had a positive and significant effect with a calculation result of 10,377 on students' work readiness (Y). Block system learning (X1) with significant project-based learning (X2) together (Silmutan) had a positive effect with an Fcal result of 55.140 with a sig of 0.00 on students' work readiness (Y)